ALMA observations of Elias 2–24: a protoplanetary disk with multiple gaps in the Ophiuchus molecular cloud - Cieza, Lucas A. (2017)
We present ALMA 1.3 mm continuum observations at 0. 2 (25 au) resolution of Elias 2–24, one of the largest and brightest protoplanetary disks in the Ophiuchus Molecular Cloud, and we report the presence of three partially resolved concentric gaps located at ∼20, 52, and 87 au from the star. We perform radiative transfer modeling of the disk to constrain its surface density and temperature radial profile and place the disk structure in the context of mechanisms capable of forming narrow gaps such as condensation fronts and dynamical clearing by actively forming planets. In particular, we estimate the disk temperature at the locations of the gaps to be 23, 15, and 12 K (at 20, 52, and 87 au, respectively), very close to the expected snowlines of CO (23–28 K) and N2 (12–15 K). Similarly, by assuming that the widths of the gaps correspond to 4–8× the Hill radii of forming planets (as suggested by numerical simulations), we estimate planet masses in the range of 0.2 1.5 – MJup, 1.0 8.0 – MJup, and 0.02 0.15 – MJup for the inner, middle, and outer gap, respectively. Given the surface density profile of the disk, the amount of “missing mass” at the location of each one of these gaps (between 4 and 20 MJup) is more than sufficient to account for the formation of such planets.